2021
DOI: 10.1002/jia2.25710
|View full text |Cite
|
Sign up to set email alerts
|

Intervening for HIV prevention and mental health: a review of global literature

Abstract: Introduction Numerous effective HIV prevention options exist, including behaviour change interventions, condom promotion and biomedical interventions, like voluntary medical male circumcision and pre‐exposure prophylaxis. However, populations at risk of HIV also face overlapping vulnerabilities to common mental disorders and severe mental illness. Mental health status can affect engagement in HIV risk behaviours and HIV prevention programmes. We conducted a narrative review of the literature on HIV prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 109 publications
1
10
0
Order By: Relevance
“…Despite growing evidence that both AGYW who sell sex and those who are young mothers experience multiple mental health challenges, there have been few interventions that holistically address these [ 5 , 36 , 37 ]. This study found that introducing an opportunity to build support, reduce isolation and provide practical and material assistance helped meet many of AGYW’s needs related to their struggles to cope with looking after their children in a context of severe economic deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing evidence that both AGYW who sell sex and those who are young mothers experience multiple mental health challenges, there have been few interventions that holistically address these [ 5 , 36 , 37 ]. This study found that introducing an opportunity to build support, reduce isolation and provide practical and material assistance helped meet many of AGYW’s needs related to their struggles to cope with looking after their children in a context of severe economic deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ACEs have been linked to alteration of the neurobiological stress–response systems [ 21 , 22 ], resulting in negative physical health outcomes, such as cancer [ 23 , 24 ], respiratory problems, such as asthma [ 25 , 26 ] and chronic obstructive pulmonary disease [ 27 , 28 ], as well as premature mortality (Brown et al, 2009). ACEs are also linked with poor mental health and substance use outcomes in the extant literature [ 29 , 30 ], both of which are linked to engagement in HIV-related behaviors, both risk and preventative behaviors [ 31 , 32 ]. There is little literature on the relationship between ACEs, sexual risk behaviors, and engagement in HIV-related care outcomes, including testing.…”
Section: Introductionmentioning
confidence: 99%
“…While structural interventions seek to address the upstream factors that cause inequities, service integration and person‐centred care acknowledge these inequities and develop service packages addressing their downstream impact [ 46 ]. For example, programs among key populations have successfully integrated HIV‐related services with mental healthcare [ 47 ], gender‐affirming care [ 48 ], harm reduction [ 29 ], STI and viral hepatitis diagnosis and treatment [ 49 , 50 , 51 ], tuberculosis [ 52 ], sexual and reproductive health [ 53 ] and services that address gender‐based violence [ 54 ]. As one specific example, through EpiC Kenya, 220 key population clients who were initially reached with services to address violence (e.g.…”
Section: Discussionmentioning
confidence: 99%